Information Ethics in Malaysia Paperless Hospital - Sulaiman, Sapiah (2006)
This paper focuses on the information ethics in Malaysian paperless hospital because of the variability of human behaviour due to the very dynamic nature of cyber space. Currently, Malaysia had implemented two paperless hospitals. These hospitals are using computer information system as a medium to improve their operation efficiency. But at the moment, there is no code of ethics for the healthcare professionals in handling the patient’s information using the computer. They only have code of conduct as a guide. This code of conduct focuses more on patient’s care. The objective of this study is to design an ethical framework towards a successful paperless hospital implementation. The data will be collected by interview and questionnaires. It is hope that the ethical framework will help to increase the efficiency of medical information system in Malaysian public paperless hospital.